Prevalence and Distribution of Human Papillomavirus Genotypes (1997–2019) and Their Association With Cervical Cancer and Precursor Lesions in Women From Southern Mexico - Luz del Carmen Alarcón‐Romero; Jorge Organista‐Nava; Yazmín Gómez‐Gómez; Julio Ortíz-Ortíz; Daniel Hernández‐Sotelo; Óscar Del Moral-Hernández; Miguel A. Mendoza‐Catalán; Ramón Antaño-Arias; Marco Antonio Leyva‐Vázquez; Natividad Sales-Linares; Verónica Antonio-Véjar; Berenice Illades‐Aguiar (2022)
Cervical cancer (CC) is the fourth most common malignancy of the female genital tract. Human Papillomavirus (HPV) is the main cause of precancerous lesions and CC cases worldwide.